Electrode montage for transcranial direct current stimulation governs its effect on symptoms and functionality in schizophrenia - Yamada, Yuji; Narita, Zui; Inagawa, Takuma; Yokoi, Yuma; Hirabayashi, Naotsugu; Shirama, Aya; Sueyoshi, Kazuki; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2023)
Backgrounds Patients with schizophrenia suffer from cognitive impairment that worsens real-world functional outcomes. We previously reported that multi-session transcranial direct current stimulation (tDCS) delivered to the left dorsolateral prefrontal cortex (DLPFC) improved daily living skills, while stimulation on the left superior temporal sulcus (STS) enhanced performance on a test of social cognition in these patients. To examine the region-dependent influence of tDCS on daily-living skills, neurocognition, and psychotic symptoms, this study compared effects of anodal stimulation targeting either of these two brain areas in patients with schizophrenia. Methods Data were collected from open-label, single-arm trials with anodal electrodes placed over the left DLPFC (N = 28) or STS (N = 15). Daily-living skills, neurocognition, and psychotic symptoms were measured with the UCSD performance-based skills assessment-brief (UPSA-B), Brief Assessment of Cognition in Schizophrenia (BACS), and Positive and Negative Syndrome Scale (PANSS), respectively. After baseline evaluation, tDCS (2 mA × 20 min) were delivered two times per day for 5 consecutive days. One month after the final stimulation, clinical assessments were repeated. Results Performance on the UPSA-B was significantly improved in patients who received anodal tDCS at the left DLPFC (d = 0.70, p < 0.001), while this effect was absent in patients with anodal electrodes placed on the left STS (d = 0.02, p = 0.939). Significant improvement was also observed for scores on the BACS with anodal tDCS delivered to the DLPFC (d = 0.49, p < 0.001); however, such neurocognitive enhancement was absent when the STS was stimulated (d = 0.05, p = 0.646). Both methods of anodal stimulation showed a significant improvement of General Psychopathology scores on the PANSS (DLPFC, d = 0.50, p = 0.027; STS, d = 0.44, p = 0.001). Conclusion These results indicate the importance of selecting brain regions as a target for tDCS according to clinical features of individual patients. Anodal stimulation of the left DLPFC may be advantageous in improving higher level functional outcomes in patients with schizophrenia. Trial registration These studies were registered within the University hospital Medical Information Network Clinical Trials Registry [(24), UMIN000015953], and the Japan Registry of Clinical Trials [(28), jRCTs032180026].